Analysis of the Role of Podcasts as a New Platform in Multiplatform Journalism in the Digital Era - Amelia, Amelia; Ningsih, Widia (Sekolah Tinggi Agama Islam Kuningan, 2024)
This study aims to analyze the role of podcasts as a new platform in multiplatform journalism, especially in presenting in-depth and critical information to audiences in Indonesia. This study uses a content analysis method on two podcast episodes: